BIBLIOTECA PUBLICĂ MODERNĂ – PRISPA COMUNITĂŢII - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
Novateca Program and the Ministry of Culture launch the start of the modernization and innovation of public libraries in the country in the first six districts from 15 - winning the first round of the Novateca Program – Ialoveni, Rezina, Şoldăneşti, Orhei, Hânceşti, Teleneşti. The event took place at the orientation conference for public libraries selected in the first round, aimed to familiarize representatives of the six districts (librarians, heads of culture department, mayors) conditions of the activity in Novateca Program, equipping libraries with equipment, training requirements for public libraries and professional development opportunities for librarians. The Orientation Conference was held in Leo Grand Hotel, on July 16 and was attended by over 300 librarians. Below we reproduce the speech of Mrs Lidia Kulikovski, libraries innovation specialist, Director of Studies and Research Department, Municipal Library "B.P. Hasdeu".